Stearic acid-based high-strength hydrophobic material and method for preparing the same

CN118995013BActive Publication Date: 2026-10-27XIAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410962344.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2026-10-27
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

[0005]本发明要解决的技术问题是克服硬脂酸作为整体疏水材料掺入混凝土后分散难,抑制水泥水化,强度降低的难题,提供了一种硬脂酸基高强疏水材料及其制备方法

Benefits of technology

(1)本发明提供了一种硬脂酸基高强疏水混凝土材料,该材料具有先释放增效剂再释放疏水固体的特点。先释放增效剂可以实现水泥基材料的高分散性,减少水泥基材料团聚现象,促进水泥水化进程,增强混凝土密实度和强度;后释放硬脂酸使其在混凝土养护前期不发挥作用并可以减弱疏水材料表面的酯性,使材料具有润湿性,能够均匀分散在混凝土中,不仅避免了局部疏水产生较大的孔隙,还能增强混凝土的整体疏水效果,增强混凝土的疏水性能及抗水、离子侵蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005063545040000011
    Figure HDA0005063545040000011
  • Figure HDA0005063545040000012
    Figure HDA0005063545040000012
Patent Text Reader

Abstract

The application relates to the technical field of concrete hydrophobic materials, in particular to a stearic acid-based high-strength hydrophobic material and a preparation method thereof, which is prepared from stearic acid, polylactic acid powder, a solvent, an emulsifier, deionized water, sodium carboxymethyl cellulose, an anti-sticking agent, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil and a synergist. The stearic acid-based high-strength hydrophobic material can be uniformly dispersed in the interior of concrete, and the interior of the concrete has the performance of overall hydrophobicity; the stearic acid-based high-strength hydrophobic material in the application can be uniformly dispersed in the interior of concrete, and the interior of the concrete has the performance that the overall hydrophobicity is relatively strong; the hydrophobicity of the concrete can be obviously improved; the outermost layer of the synergist can obviously improve the strength of the concrete; the hydrophobic-synergistic material prepared by integrating the hydrophobicity and the synergism can greatly contribute to the hydrophobicity, the strength, the durability and the service life of the cement concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete hydrophobic materials technology, and more specifically, to a stearic acid-based high-strength hydrophobic material and its preparation method. Background Technology

[0002] Concrete forms the foundation of modern construction and plays a vital role in the building industry, including marine structures, bridge engineering, and infrastructure in salt lakes and saline-alkali land areas. However, concrete's porous physical structure, coupled with its hydrophilic, permeable, and hygroscopic properties, makes it susceptible to durability problems due to water erosion in practical engineering projects, resulting in significant economic losses. Currently, one effective measure to address this issue is to modify concrete to be hydrophobic, enabling it to effectively limit water absorption and permeation.

[0003] There are two main methods for hydrophobic modification of concrete: surface hydrophobic coating modification and overall hydrophobic modification. Surface hydrophobic coating modification involves spraying hydrophobic materials onto the surface of the formed concrete, preventing external water from penetrating into the concrete and achieving a water-blocking effect. This is currently the most widely used hydrophobic technology in concrete engineering in my country. However, hydrophobic coatings generally suffer from problems such as fragile surface structure, poor wear resistance, easy peeling, susceptibility to chemical corrosion, and difficulty in large-area coverage. Furthermore, their subsequent maintenance requires significant manpower, material resources, and financial investment. To effectively overcome the problems faced by hydrophobic coatings, research on overall hydrophobic materials for concrete is of great significance. Overall hydrophobic modification involves incorporating hydrophobic materials into the concrete interior. By altering the surface tension within pores and cracks, the concrete achieves an overall hydrophobic effect. Even if the surface wears down and cracks appear, its impermeability remains unaffected, it is not easily deteriorated, and it does not require regular maintenance.

[0004] Stearic acid, due to its low price and excellent hydrophobic properties, can be used as a good hydrophobic material. However, when used as a monolithic hydrophobic material in concrete, it has the following limitations: First, stearic acid is non-wetting, making it difficult to disperse evenly in concrete at room temperature, leading to large local pores in the concrete. Second, the direct incorporation of stearic acid inhibits the early hydration process of cement and prevents the bonding of cement particles, which is a key factor leading to a decrease in the mechanical properties of concrete. These shortcomings of stearic acid as an internal admixture as a monolithic hydrophobic material limit its application in practical engineering, and the concrete strength produced is difficult to meet the application standards of practical engineering projects. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the difficulties of dispersing stearic acid as a whole hydrophobic material in concrete, inhibiting cement hydration and reducing strength. The present invention provides a stearic acid-based high-strength hydrophobic material and its preparation method.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A stearic acid-based high-strength hydrophobic material is prepared from stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist.

[0007] Furthermore, the mass percentages of stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist are 15%~20%, 14%~18%, 20%~30%, 1%~2%, 20%~25%, 0.3%~0.5%, 5%~6%, 1%~1.5%, 0.6%~1%, 0.4%~0.6%, 1%~2.4%, 1.2%~1.5%, and 5%~7%, respectively.

[0008] Furthermore, the stearic acid is in powder form with a particle size of 200 mesh, a density of 0.82 g / ml, a melting point of 69~70℃, a moisture content of 0.19%wt, and is hydrophobic.

[0009] Furthermore, the solvent is any one or a combination of chloroform, acetone, and ethanol.

[0010] Furthermore, the emulsifier is any one of polysorbate or polyglycerol fatty acid ester.

[0011] Furthermore, the anti-adhesive is either glyceryl monostearate or talc.

[0012] This invention also provides a method for preparing a stearic acid-based high-strength hydrophobic material, comprising the following steps: S1: Weigh stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist; S2: Pour polyethylene glycol and chitosan into water, stir and mix, then add triethyl citrate to the mixture and stir magnetically to obtain mixed emulsion A; S3: Add the anti-adhesion agent and iron oxide to the mixed emulsion A in sequence, and stir magnetically to obtain the mixed colored emulsion B; S4: Place polylactic acid powder in a container, add solvent to the container containing polylactic acid powder, and magnetically stir at room temperature to obtain polylactic acid mixture C; S5: Add emulsifier and deionized water to polylactic acid mixture C, stir magnetically at room temperature, remove solvent by rotary evaporation, and obtain polylactic acid mixed emulsion D; S6: Add sodium carboxymethyl cellulose to polylactic acid mixed emulsion D, continue stirring, and then filter to obtain polylactic acid emulsion E; S7: Slowly pour the mixed colored emulsion B into the stirred polylactic acid emulsion E and continue stirring. Add methyl silicone oil 5-10 minutes before the end of stirring to obtain the colored coating crude liquid F. S8: While stirring, sieve the colored coating crude liquid F to obtain the colored coating liquid G; S9: Add coating solution G to stearic acid in batches while stirring to obtain stearic acid-based mixture H.

[0013] S10: The stearic acid-based mixture H is placed in a drying oven for drying, grinding and separation, and sieved to obtain the stearic acid-based hydrophobic material I.

[0014] S11: Spray concrete enhancer onto stearic acid-based hydrophobic material I, dry it, repeat the process 3 times, and sieve it to obtain crude stearic acid-based high-strength hydrophobic material J.

[0015] S12: Take out the crude product J of stearic acid-based high-strength hydrophobic material, sieve it, and obtain stearic acid-based high-strength hydrophobic material.

[0016] Furthermore, in steps S9 and S10: Stearic acid was placed in an environmental chamber, and the temperature inside the chamber was controlled at 40~50℃. The supply rate of the colored coating solution G was adjusted to 15g / min / kg~25g / min / kg. After stirring in the environmental chamber for 1h~2h, the mixture was removed and dried in an oven at 40℃~50℃ for 2h to obtain stearic acid-based hydrophobic material I.

[0017] Furthermore, in step S8, the colored coating crude liquid F passes through a 100-mesh sieve; in step S10, the stearic acid-based mixture H passes through a 40-60-mesh sieve; and in step S11, the stearic acid-based high-strength hydrophobic material crude product J passes through a 30-40-mesh sieve.

[0018] In this solution, the synergist can activate the cementitious materials, provide more nucleation sites for hydration products, promote the hydration process of the cementitious materials, and significantly improve the long-term strength of concrete. Simultaneously, the bridging effect between cement particles, hydration products, and the synergist can improve the rheological properties and early strength of the cementitious materials.

[0019] Iron oxide is not only used as a pigment, but trace amounts of iron oxide can also affect the formation of cement hydration products. When iron oxide is present, more calcium ferrate hydrate (CFH) will be generated. This hydrate can fill the pores in the cement colloid to improve the density of concrete. At the same time, it will also accelerate the hydration reaction of cement, promote the formation of calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), and improve the strength of concrete.

[0020] The carboxyl groups in the stearic acid released during the later stages of coating can react with the hydroxyl groups in concrete to form hydrophobic tails that branch into the concrete, changing it from hydrophilic to hydrophobic. Even if the surface is worn, the newly exposed concrete will still exhibit hydrophobicity. At the same time, stearic acid also reacts with calcium hydroxide in the concrete, promoting cement hydration by consuming calcium hydroxide.

[0021] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention provides a stearic acid-based high-strength hydrophobic concrete material, which features the characteristic of releasing an synergist first and then releasing a hydrophobic solid. The release of the synergist first can achieve high dispersibility of cement-based materials, reduce the agglomeration of cement-based materials, promote the cement hydration process, and enhance the density and strength of concrete; the release of stearic acid later prevents it from playing a role in the early stage of concrete curing and can weaken the esterification of the surface of the hydrophobic material, making the material wettable and able to be evenly dispersed in concrete. This not only avoids the formation of large pores due to local hydrophobicity, but also enhances the overall hydrophobic effect of concrete, and enhances the hydrophobic performance and resistance to water and ion erosion of concrete.

[0022] (2) The coating preparation of the stearic acid-based high-strength hydrophobic material of the present invention not only changes the non-wetting property of stearic acid, but also enables the controlled release of the internal hydrophobic material under alkaline conditions of concrete, so that the hydrophobic stearic acid does not play a role in the early stage of concrete curing, thereby solving the problem of hydrophobic materials inhibiting concrete hydration. Moreover, the coating material prepared by the present invention has good environmental protection properties, belongs to environmentally friendly materials, can be biodegraded, and reduces the pollution of the environment by waste concrete.

[0023] (3) During the material preparation process, the material is passed through two different sieves. By controlling the mesh size of the sieves, not only can the coating thickness be controlled, but also the release time of stearic acid can be controlled, reducing the impact of premature release of hydrophobic material on the early hydration of concrete. It can also control the overall size of the stearic acid-based high-strength hydrophobic material, avoiding the formation of large pores in the concrete due to excessive material size, which would affect the hydrophobic effect and the strength of the concrete. At the same time, the stearic acid released after early hydration can fill the pores of the concrete, making the concrete denser.

[0024] (4) The addition of trace amounts of iron oxide in the coating liquid can not only determine the effect of hydrophobic material coating, but also accelerate the hydration of cement in concrete. The hydration product, calcium ferrate hydrate (CFH), can fill the pores of cementitious materials and improve the density and strength of concrete. Attached Figure Description

[0025] Figure 1 This is an electron micrograph of the stearic acid used in the embodiments of the present invention; Figure 2This is an electron microscope image of the stearic acid-based high-strength hydrophobic material used in the embodiments of the present invention; Figure 3 This is an electron microscope image of the stearic acid-based high-strength hydrophobic material used in the embodiments of the present invention 3 days after application; Figure 4 This is an electron microscope image of the stearic acid-based high-strength hydrophobic material used in the embodiments of the present invention 28 days after application. Detailed Implementation

[0026] To enable those skilled in the art to better understand the invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Furthermore, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessary confusion regarding the concepts disclosed in the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0027] The stearic acid-based high-strength hydrophobic material of this invention has strong hydrophobic properties, which can significantly improve the hydrophobicity of concrete. Furthermore, the outermost coating of the synergist can significantly improve the strength of concrete. Thus, the prepared hydrophobic-synergistic material can make a significant contribution to the hydrophobicity, strength, durability, and service life of cement concrete.

[0028] The stearic acid-based high-strength hydrophobic material provided by this invention is prepared from stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist. The solvent is any one or a combination of chloroform, acetone, and ethanol; the emulsifier is any one of polysorbate and polyglycerol fatty acid ester; and the anti-adhesive is any one of glyceryl monostearate and talc.

[0029] Polylactic acid (PLA) emulsions are prepared from PLA powder, solvent, emulsifier, deionized water, and sodium carboxymethyl cellulose. The solvent can be any one or a combination of chloroform, acetone, and ethanol, and the emulsifier can be polysorbate or polyglycerol fatty acid ester. The preparation method of PLA emulsions is as follows: PLA powder is placed in a container, and the solvent is added to the container containing PLA powder. The mixture is magnetically stirred at room temperature to obtain a PLA mixture. The emulsifier and deionized water are added to the PLA mixture, and the mixture is magnetically stirred at room temperature. The solvent is removed by rotary evaporation to obtain a PLA mixed emulsion. Sodium carboxymethyl cellulose is added to the PLA mixed emulsion, and the mixture is stirred continuously. The mixture is then filtered to obtain the PLA emulsion.

[0030] The coating liquid prepared from polylactic acid emulsion can not only form a uniform coating on the surface of stearic acid, making stearic acid wettable, but also adsorb synergists more uniformly, improving the workability and strength of fresh concrete; the coating of synergists can improve the fluidity and workability of cement-based materials in concrete and promote the hydration of cement-based materials.

[0031] The following are specific embodiments of the present invention. It should be noted that the present invention is not limited to the following specific embodiments. All equivalent modifications made based on the technical solutions of this application fall within the protection scope of the present invention. Example 1

[0032] This embodiment provides a stearic acid-based high-strength hydrophobic material, which, by weight fraction, is made from the following raw materials: 17.5% stearic acid, 16% polylactic acid powder, 25% solvent, 1.5% emulsifier, 22.5% deionized water, 0.4% sodium carboxymethyl cellulose, 5.5% glyceryl monostearate, 1.25% triethyl citrate, 0.8% iron oxide, 0.5% polyethylene glycol, 1.7% chitosan, 1.35% methyl silicone oil, and 6% synergist.

[0033] The preparation method of the stearic acid-based high-strength hydrophobic material in this embodiment is carried out according to the following steps: S1: Weigh each raw material according to the proportions and set aside; S2: Pour polyethylene glycol and chitosan into water, stir and mix, then add triethyl citrate to the mixture and stir magnetically to obtain mixed emulsion A; S3: Add the anti-adhesion agent and iron oxide to the mixed emulsion A in sequence, and stir magnetically to obtain the mixed colored emulsion B; S4: Place polylactic acid powder in a container, add solvent to the container containing polylactic acid powder, and magnetically stir at room temperature to obtain polylactic acid mixture C; S5: Add emulsifier and deionized water to polylactic acid mixture C, stir magnetically at room temperature, remove solvent by rotary evaporation, and obtain polylactic acid mixed emulsion D; S6: Add sodium carboxymethyl cellulose to polylactic acid mixed emulsion D, continue stirring, and then filter to obtain polylactic acid emulsion E; S7: Slowly pour the mixed colored emulsion B into the stirred polylactic acid emulsion E and continue stirring. Add methyl silicone oil 5-10 minutes before the end of stirring to obtain the colored coating crude liquid F. S8: While stirring, sieve the colored coating crude liquid F to obtain the colored coating liquid G; S9: Add coating solution G to stearic acid in batches while stirring to obtain stearic acid-based mixture H.

[0034] S10: The stearic acid-based mixture H is placed in a drying oven for drying, grinding and separation, and sieved to obtain the stearic acid-based hydrophobic material I.

[0035] S11: Spray concrete enhancer onto stearic acid-based hydrophobic material I, dry it, repeat the process 3 times, and sieve it to obtain crude stearic acid-based high-strength hydrophobic material J.

[0036] S12: Take out the crude product J of stearic acid-based high-strength hydrophobic material, sieve it, and obtain stearic acid-based high-strength hydrophobic material.

[0037] Performance testing: To verify that the stearic acid-based high-strength hydrophobic material of this embodiment has good performance, the stearic acid-based high-strength hydrophobic material prepared in this embodiment was added to the mixing equipment along with cement and mixed. The weight admixture was 0.3% of the cement weight. The resulting concrete was subjected to performance testing, including compressive strength test, flexural strength test, water absorption test, and droplet roll-off test.

[0038] The experiment used C40 concrete as the object, ordinary Portland cement of type PO42.5, medium sand with a fineness modulus of 2.7, and continuously graded crushed stone of 5mm to 25mm.

[0039] The compressive strength of concrete was tested in accordance with the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019).

[0040] The water absorption rate test method shall be carried out in accordance with the test method for water absorption rate of concrete specified in the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019).

[0041] The droplet rolling test was conducted by increasing or decreasing the droplet volume.

[0042] The hydrophobic material dosage was 0.3% of the cement dosage. The performance test results of this embodiment are shown in Table 1. Example 2

[0043] This embodiment provides a stearic acid-based high-strength hydrophobic material, which is made from the following raw materials by weight fraction: 20% stearic acid, 14% polylactic acid powder, 20% solvent, 2% emulsifier, 24% deionized water, 0.3% sodium carboxymethyl cellulose, 6% anti-adhesive, 1.2% triethyl citrate, 1% iron oxide, 0.4% polyethylene glycol, 0.5% chitosan, 1.4% methyl silicone oil, and 7% synergist.

[0044] The types and amounts of raw materials required in this embodiment are the same as in Embodiment 1.

[0045] The preparation method of the stearic acid-based high-strength hydrophobic material in this embodiment is basically the same as that in Example 1.

[0046] The performance testing process in this embodiment is basically the same as in embodiment 1. The amount of hydrophobic material is 0.5% of the amount of cement. The performance test results of this embodiment are shown in Table 1. Example 3

[0047] This embodiment provides a stearic acid-based high-strength hydrophobic material, which, by weight fraction, is made from the following raw materials: 15% stearic acid, 18% polylactic acid powder, 28.8% solvent, 2% emulsifier, 20% deionized water, 0.5% sodium carboxymethyl cellulose, 6% anti-adhesive, 1.5% triethyl citrate, 0.6% iron oxide, 0.4% polyethylene glycol, 1% chitosan, 1.2% methyl silicone oil, and 5% synergist.

[0048] The types and amounts of raw materials required in this embodiment are the same as in Embodiment 1.

[0049] The preparation method of the stearic acid-based high-strength hydrophobic material in this embodiment is basically the same as that in Example 1.

[0050] The performance testing process in this embodiment is basically the same as in embodiment 1. The amount of hydrophobic material is 0.7% of the amount of cement. The performance test results of this embodiment are shown in Table 1. Example 4

[0051] This embodiment provides a stearic acid-based high-strength hydrophobic material, which, by weight fraction, is made from the following raw materials: 17.4% stearic acid, 17% polylactic acid powder, 25% solvent, 1.7% emulsifier, 22% deionized water, 0.3% sodium carboxymethyl cellulose, 5.7% anti-adhesive, 1.3% triethyl citrate, 0.7% iron oxide, 0.5% polyethylene glycol, 1.2% chitosan, 1.2% methyl silicone oil, and 6% synergist.

[0052] The types and amounts of raw materials required in this embodiment are the same as in Embodiment 1.

[0053] The preparation method of the stearic acid-based high-strength hydrophobic material in this embodiment is basically the same as that in Example 1.

[0054] The performance testing process in this embodiment is basically the same as in embodiment 1. The amount of hydrophobic material is 0.5% of the amount of cement. The performance test results of this embodiment are shown in Table 1.

[0055] In the above embodiments, polysorbate or gelatin were used as emulsifiers, and the effects were basically the same.

[0056] Comparative Example 1: This comparative example provides ordinary concrete with the same mix proportions as in Example 1, but the component content of its raw materials is increased proportionally according to the mix proportions in Example 1, so that the sum of the weight parts of the raw materials is 100%.

[0057] The required amounts of each component in the concrete in this comparative example are the same as in Example 1.

[0058] The performance testing process of this comparative example is basically the same as that of Example 1, and the performance test results of this comparative example are shown in Table 1.

[0059] Comparative Example 2: In this comparative example, stearic acid is incorporated into concrete. The only difference is that the stearic acid is not modified as described above in this comparative example. The content of other raw materials is increased proportionally according to the proportions in Example 1, so that the sum of the weight parts of the raw materials is 100%.

[0060] The performance testing process for this comparative example is basically the same as that for Example 1.

[0061] The required amounts of each component in the concrete in this comparative example are the same as in Example 1. The amount of stearic acid is 0.5% of the amount of cement. The performance test results of this comparative example are shown in Table 1.

[0062] Table 1. Test results of hydrophobic material properties (all are changes relative to the reference concrete).

[0063] As shown in Table 1: The comparison of Examples 1-4 shows that the stearic acid-based high-strength hydrophobic materials in Examples 1-4 can significantly improve the compressive strength of concrete. The 28-day compressive strength of all four examples is more than 114.1% of the strength of ordinary concrete in Comparative Example 1. The reduction in water absorption rate after 72 hours is also high, and the droplet roll-off rate at 5°C also shows high performance, indicating good hydrophobic effect.

[0064] A comparison of Examples 1-4 and Comparative Examples 1 and 2 shows that, compared to ordinary concrete, the stearic acid-based high-strength hydrophobic materials provided in Examples 1-4 exhibit significant hydrophobic effects when used as overall hydrophobic materials for concrete, and the 3-day and 28-day compressive strengths of the concrete are improved. A comparison with Comparative Example 2 reveals that the modification of stearic acid in this patent significantly enhances its hydrophobic properties and strength. Examples 1-4 demonstrate superior performance compared to existing materials, ensuring the hydrophobic properties of concrete while simultaneously strengthening its strength and improving its durability and impermeability.

[0065] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A stearic acid-based high-strength hydrophobic material, characterized in that, It is prepared from stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist. The mass percentages of stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist are 15%~20%, 14%~18%, 20%~30%, 1%~2%, 20%~25%, 0.3%~0.5%, 5%~6%, 1%~1.5%, 0.6%~1%, 0.4%~0.6%, 1%~2.4%, 1.2%~1.5%, and 5%~7%, respectively. The preparation method of the stearic acid-based high-strength hydrophobic material includes the following steps: S1: Weigh stearic acid, polylactic acid powder, solvent, emulsifier, deionized water, sodium carboxymethyl cellulose, anti-adhesive, triethyl citrate, iron oxide, polyethylene glycol, chitosan, methyl silicone oil, and synergist; S2: Pour polyethylene glycol and chitosan into water, stir and mix, then add triethyl citrate to the mixture and stir magnetically to obtain mixed emulsion A; S3: Add the anti-adhesion agent and iron oxide to the mixed emulsion A in sequence, and stir magnetically to obtain the mixed colored emulsion B; S4: Place polylactic acid powder in a container, add solvent to the container containing polylactic acid powder, and magnetically stir at room temperature to obtain polylactic acid mixture C; S5: Add emulsifier and deionized water to polylactic acid mixture C, stir magnetically at room temperature, remove solvent by rotary evaporation, and obtain polylactic acid mixed emulsion D; S6: Add sodium carboxymethyl cellulose to polylactic acid mixed emulsion D, continue stirring, and then filter to obtain polylactic acid emulsion E; S7: Slowly pour the mixed colored emulsion B into the stirred polylactic acid emulsion E and continue stirring. Add methyl silicone oil 5-10 minutes before the end of stirring to obtain the colored coating crude liquid F. S8: While stirring, sieve the colored coating crude liquid F to obtain the colored coating liquid G; S9: Add coating solution G to stearic acid in batches while stirring to obtain stearic acid base mixture H; S10: Stearic acid-based mixture H is placed in a drying oven for drying, grinding and separation, and sieved to obtain stearic acid-based hydrophobic material I; S11: Spray concrete enhancer onto stearic acid-based hydrophobic material I, dry it, repeat the process 3 times, and sieve it to obtain crude stearic acid-based high-strength hydrophobic material J. S12: Take out the crude product J of stearic acid-based high-strength hydrophobic material, sieve it, and obtain stearic acid-based high-strength hydrophobic material.

2. The stearic acid-based high-strength hydrophobic material according to claim 1, characterized in that: The stearic acid is in powder form with a particle size of 200 mesh, a density of 0.82 g / ml, a melting point of 69~70℃, a moisture content of 0.19%wt, and is hydrophobic.

3. The stearic acid-based high-strength hydrophobic material according to claim 1, characterized in that: The solvent is any one or a combination of chloroform, acetone, and ethanol.

4. The stearic acid-based high-strength hydrophobic material according to claim 1, characterized in that: The emulsifier is any one of polysorbate or polyglycerol fatty acid ester.

5. The stearic acid-based high-strength hydrophobic material according to claim 1, characterized in that: The anti-adhesion agent is either glyceryl monostearate or talc.

6. The stearic acid-based high-strength hydrophobic material according to claim 1, characterized in that, In steps S9 and S10: Stearic acid was placed in an environmental chamber, and the temperature inside the chamber was controlled at 40~50℃. The supply rate of the colored coating solution G was adjusted to 15g / min / kg~25g / min / kg. After stirring in the environmental chamber for 1h~2h, the mixture was removed and dried in an oven at 40℃~50℃ for 2h to obtain stearic acid-based hydrophobic material I.

7. The stearic acid-based high-strength hydrophobic material according to claim 1, characterized in that, In step S8, the colored coating crude liquid F passes through a 100-mesh sieve; in step S10, the stearic acid-based mixture H passes through a 40-60-mesh sieve; and in step S11, the stearic acid-based high-strength hydrophobic material crude product J passes through a 30-40-mesh sieve.

Citation Information

Patent Citations

  • Admixture for improving impermeability of concrete and preparation method thereof

    CN112979207A

  • Composite hydrophobic agent, preparation method and application thereof

    CN113354325A